2021
DOI: 10.1186/s12933-021-01382-8
|View full text |Cite
|
Sign up to set email alerts
|

Body weight changes in patients with type 2 diabetes and a recent acute coronary syndrome: an analysis from the EXAMINE trial

Abstract: Background Patients with type 2 diabetes (T2D) may experience frequent body weight changes over time. The prognostic impact of these weight changes (gains or losses) requires further study. Aims To study the associations between changes in body weight (intentional or unintentional) with subsequent outcomes. Methods The EXAMINE trial included 5380 patients with T2D and a recent acute coronary syndrome, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…Ten studies [ 9 , 11 , 18 , 22 , 24 , 28 , 31 34 ] excluded individuals with pre-existing CV comorbidities. One study [ 19 ] included T2DM patients with a recent acute coronary syndrome. Ten studies [ 8 , 9 , 11 , 12 , 18 , 20 23 , 35 ] used a more than 2-year weight change interval to make sure that the change in weight was sustained.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies [ 9 , 11 , 18 , 22 , 24 , 28 , 31 34 ] excluded individuals with pre-existing CV comorbidities. One study [ 19 ] included T2DM patients with a recent acute coronary syndrome. Ten studies [ 8 , 9 , 11 , 12 , 18 , 20 23 , 35 ] used a more than 2-year weight change interval to make sure that the change in weight was sustained.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 18 studies that investigated the association between weight loss and risk of all-cause mortality (outcomes are presented in Additional file 2 : Table S3), 14 studies[ 8 12 , 19 21 , 23 , 27 , 29 , 32 , 35 , 38 ] found that weight loss was associated with an increased risk of all-cause mortality (HR [95% CI] ranging from 1.21 [1.03–1.41] to 5.6 [3.96–7.91]). Other 3 studies [ 7 , 28 , 31 ] found no association between weight loss and mortality.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations